1972
DOI: 10.3382/ps.0511548
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Protein Grower Diet on the Reproductive Performance of Turkey Breeder Toms

Abstract: Sixty Marston Broad White toms were used in each of two experiments (hatched February and late July) and were equally divided among six floor pens (1.5X2.4 m.). All birds were fed a commercial type starter diet through the tenth week of age. From the eleventh through the twenty-fourth week of age, one-half of the birds were fed a low protein grower diet (10.2 percent protein) while the remaining birds were fed the control grower (21 percent protein). Beginning with the twenty-fifth week all birds received a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
2

Year Published

1974
1974
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
(6 reference statements)
3
6
2
Order By: Relevance
“…These data indicate that the limitation of protein intake in groups 1 and 2 was the motivating force in the reduction of body weight since group 3 that was limited in energy alone grew as rapidly as the toms in group 4 receiving the control diet. These results are in agreement with those of Summers et al (1968) who found that level of protein influenced weight gain regardless of dietary energy level, and Voitle et al (1972) who observed that toms receiving a protein-restricted diet were 36-38 percent lighter than the controls at 24 weeks of age. On the other hand, Anderson et al (1963) restricted feed intake (energy and protein) of toms from 12 to 24 weeks of age and noted significantly reduced body weights, and also Touchburn and Brown (1972) who found energy and protein restricted birds to weigh 73 to 83 percent of their full-fed counterparts at 26 weeks of age.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These data indicate that the limitation of protein intake in groups 1 and 2 was the motivating force in the reduction of body weight since group 3 that was limited in energy alone grew as rapidly as the toms in group 4 receiving the control diet. These results are in agreement with those of Summers et al (1968) who found that level of protein influenced weight gain regardless of dietary energy level, and Voitle et al (1972) who observed that toms receiving a protein-restricted diet were 36-38 percent lighter than the controls at 24 weeks of age. On the other hand, Anderson et al (1963) restricted feed intake (energy and protein) of toms from 12 to 24 weeks of age and noted significantly reduced body weights, and also Touchburn and Brown (1972) who found energy and protein restricted birds to weigh 73 to 83 percent of their full-fed counterparts at 26 weeks of age.…”
Section: Resultssupporting
confidence: 94%
“…This difference, however, vanished after a few weeks when the toms in all groups reached essentially the same average weight. This experience is not unlike that of Voitle et al (1972) who observed protein-restricted males to be ejaculated more easily than males receiving a control diet. Dietary restriction had no appar-ent effect on the potency of semen in fertilization.…”
Section: Resultscontrasting
confidence: 54%
“…The pattern of the curves (Figure 1) suggests that sperm storage in the female reproductive tract might have been superior during the first nine weeks of egg production, since the differences in fertility as a result of the dilutions at that time were minimal (Table 6). Voitle et al (1972) reported higher but nonsignificant improvements in fertility for males which had been restricted from 11 to 24 weeks of age by feeding a low protein diet, over that obtained with full-fed males given a higher protein level.…”
Section: Resultsmentioning
confidence: 61%
“…They also suggested that the age and degree of sexual development of males at the time they were subjected to different light treatments would affect subsequent reproductive performance. Voitle et al (1972) found that feeding turkey males a low protein grower diet from 11 through 24 weeks of age resulted in body weights 3 5% lighter than full-fed controls receiving a 21% protein diet. However, within a few weeks after being returned to full feed, the previously restricted males were essentially the same body weight as the controls.…”
Section: Introductionmentioning
confidence: 94%
“…Dietary protein levels for turkey breeder hens have been reported to be satisfactory for reproductive performance at levels ranging from 10% to 21% (Jensen and McGinnis, 1961;Wahid et al, 1967;Minear et al, 1970;Atkinson et al, 1970;Luther and Waldroup, 1970;Bradley et al, 1971;Jensen, 1973). Voitle et al (1972), reported that reproductive efficiency of Marston Broad White breeder toms could be improved by feeding a proteinrestricted diet of 10.2 percent protein during the growing period versus a normal protein diet of 21.0 percent. At 24 weeks of age, the restricted torn body weights were 36 to 38 percent lighter than toms reared on the higher protein diet.…”
Section: Introductionmentioning
confidence: 96%